Just how free is a free choice of law in contract in the EU?. (4th May 2017) - Mankowski, Peter
Abstract : Free choice of law appears to be the pivot and the unchallenged champion of the private international law of contracts. Yet to stop at this would be a fallacy and would disregard the challenges it has to face. Those challenges come from different quarters. In B2C contracts in the EU not only the more favourable law principles as enshrined in Article 6(2) of the Rome I Regulation must be observed, but also any requirements which the Unfair Contract Terms Directive imposes. Transparency in particular ranks high. In Verein für Konsumenteninformation v Amazon the Court of Justice of the European Union has imposed duties on businesses and professionals to inform their consumer customers about at least the existence and the basic structure of the more favourable law principle. This landmark decision might not stand on ground as firm as it implies at first sight. Its fundament might be shaken by inconsistency. But practice has to comply with it and has to observe its consequences. On a more abstract level, it raises ample necessity to reflect about the modern-day structure of "free" choice of law. In this context, it is argued that the system established for parties' choice of law in the Rome I Regulation does not allow for a content review of choice of law agreements.